Janus Kinase Inhibitors in the Treatment of Type I Interferonopathies: A Case Series From a Single Center in China - Li, Wendao; Wang, Wei; Wang, Wei; Zhong, Linqing; Gou, Lijuan; Wang, Changyan; Ma, Jingran; Quan, Meiying; Jian, Shan; Tang, Xiaoyan; Zhang, Yu; Wang, Lin; et al. (Frontiers in Immunology, 2022)
Objective: To assess the efficacy and safety of 2 Janus kinase (JAK) inhibitors (jakinibs) tofacitinib and ruxolitinib in the treatment of type I interferonopathies patients including STING-associated vasculopathy with onset in infancy (SAVI), Aicardi-Goutières syndrome (AGS), and spondyloenchondrodysplasia with immune dysregulation (SPENCD). Methods: A total of 6 patients were considered in this study: 2 patients with SAVI, 1 patient with AGS1, 1 patient with AGS7, and 2 patients with SPENCD. Clinical manifestations, laboratory investigations, radiology examinations, treatment, and outcomes were collected between November 2017 and November 2021 in Peking Union Medical College Hospital. The disease score for patients with SAVI and AGS scale for patients with AGS were documented. The expression of 6 interferon-stimulated genes (ISGs) was assessed by real-time PCR. Results: Three patients (1 patient with SAVI, 2 patients with AGS) were treated with ruxolitinib and 3 patients (1 patient with SAVI, 2 patients with SPENCD) were treated with tofacitinib. The mean duration of the treatment was 2.5 years (1.25-4 years). Upon treatment, cutaneous lesions and febrile attacks subsided in all affected patients. Two patients discontinued the corticoid treatment. Two patients with SAVI showed an improvement in the disease scores (p < 0.05). The erythrocyte sedimentation rate normalized in 2 patients with AGS. The interferon score (IS) was remarkably decreased in 2 patients with SPENCD (p < 0.01). Catch-up with growth and weight gain were observed in 3 and 2 patients, respectively. Lung lesions improved in 1 patient with SAVI and remained stable in 3 patients. Lymphopenia was found in 3 patients during the treatment without severe infections. Conclusion: The JAK inhibitors baricitinib and tofacitinib are promising therapeutic agents for patients with SAVI, AGS and SPENCD, especially for the improvement of cutaneous lesions and febrile attacks. However, further cohort studies are needed to assess the efficacy and safety.